Analysis of the Impact of Erroneous Land Measurement Results on Construction Project Implementation (Study Case of the Integrated Sports Area Development for South Kalimantan Province) - Pamungkas, Siddiq Wahyu; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Development problems in Indonesia are divided into two major parts, namely the problem of development objects and the problem of subjects who will carry out development. Problems originating from the subject of development are in terms of land acquisition. Thus, land acquisition efforts for these purposes need to be handled properly and carried out by taking into account the role of land in human life and the principle of respect for legal rights to land. The Public Works and Spatial Planning Office of South Kalimantan Province has planned the development area of the government center in Banjarbaru City. One of them is the design of a more representative sports area. In 2022 and 2023, the land acquisition of the Integrated Sports Area Phase I and II has been carried out together with the implementation team of the South Kalimantan Provincial BPN Office. In connection with this achievement, this research is important because the land acquisition process is related to project productivity which causes the construction of the Integrated Sports Area to be hampered. This research focuses on the variable factors of the stages and technical implementation of land acquisition (Inventory and identification of land tenure, ownership, use, and utilization) and internal factors (Verification and improvement of land parcel maps and / or nominative lists by the Chief Land Acquisition Executive if there are objections to the results of inventory and identification), namely the results of land measurement. Analysis of measurement error results by finding the amount of linear shift to determine the standard deviation of comparison of measurement results of two different tools. The results of the questionnaire will be tested for validity and reliability to determine the level of importance of the measurement results from respondents followed by Relative Importance Index (RII) Analysis to find out what dominant impacts affect the Construction project, these two methods are taken into consideration in determining mitigation efforts for land measurement inaccuracies on the physical development process. The impact of KOT land measurement errors on delays in physical development plans is obtained dominant factors based on the rank of RII values, namely the compensation value (X1.2), development project costs (X2.4), design changes (X2.3), plant growth and affected buildings (X1.3), development permits (X2.5), land certification (settlement) (X1.4), development process (X2.1), smooth land acquisition (X1.1) while delays (X2.2) are below 75% of the RII value so they are not included as priority factors to be mitigated.